Genotypic Variation in Maintenance of Leaf Water Potential in Rice - O'Toole, J.C.; Moya, T.B. (Wiley, 1978)
Rice (Oryza sativa L.), a semiaquatic species, is best adapted to culture in a submerged soil. Rice grown in rain fed environments may suffer significant yield losses due to drought. At the International Rice Research Institute, Philippines, thousands of genotypes are screened annually for drought resistance in upland fields during the dry season. We monitored the leaf water potential of 17 diverse genotypes to investigate the physiological basis for genotypic differences obtained through visual scoring of plant symptoms. The genotypes were grown in small plots, established by sprinkler irrigation. Twenty‐two ays after emergence, irrigation was stopped and a stress period initiated. Thirty‐nine days later, differentiation of genotypes was considered optimal by visual scoring and intensive diurnal sampling of leaf water potential began. Significant differences were detected among the genotypes for maintenance of relatively high leaf water potential. Two visual scoring techniques, one based on leaf rolling and the other on leaf tip drying, were highly correlated with maintenance of leaf water potential. Visual scoring based on leaf rolling behavior appeared to be influenced by diurnal adjustment of the pressure potential. The integral for the day (—bar.day) was quite effective in separation of cultivars for maintenance of high leaf water potential throughout the day and highly correlated with ranking by visual scoring.